Pengaruh Value Co-Creation Terhadap Loyalitas Pelanggan: (Studi Pada Mahasiswa Pengguna Gojek di Universitas Sumatera Utara) - Yabes Abi, Wilmer Nicholas; Pertiwi Matondang, Rahmatika; Agung Harahap, Abiyyu; Margaretta Batubara, Desy; Nazwa Fahira, Tengku; Mulyati Siregar, Afrila; Marakali Siregar, Onan (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2024)
In the digital era, technology companies like Gojek must continuously improve service quality and create greater value to maintain customer loyalty. This study aims to understand how value co-creation practices can enhance customer loyalty among Gojek users who are students at the University of North Sumatra. This research uses a quantitative approach by distributing questionnaires to 100 students from 15 faculties who actively use Gojek services in the last three months. Data analysis was performed using simple linear regression through the SPSS application. The results of the study indicate that value co-creation has a positive and significant impact on customer loyalty, with a t-value of 9.773, which is greater than the t-table value of 1.66023, and a significance level of 0.000. Thus, value co-creation has been proven to enhance customer loyalty through active participation, interaction, and knowledge sharing between customers and service providers.